Perlindungan Hukum terhadap Karya Seni Melalui Media Mural - Deviana Utami Wijaya; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Warmadewa Press, 2022)
A work of art is an artistic creation of an aesthetic object. Usually, it can be depicted in the form of sculptures, but can also be in the form of objects specially designed for aesthetic purposes and their uses. This research aims to analyze and regulate legal regulations and protections related to mural art in Indonesia. The method used is a normative legal research method. Legal arrangements regarding legal arrangements related to mural art in Indonesia are contained in the 1945 Constitution of the Republic of Indonesia Article 28 I and 28 J, Law No.39/1999 on Human Rights, Law no. 9 of 1998 concerning Expressing opinions in public and Law No. 12 of 2005 concerning Civil and Political Rights. The legal protection given to mural artworks is more or less the same as the regulation, except that not all mural artworks can be protected, if the mural art violates the applicable legal norms then it can be said that Vandalism is regulated in the Criminal Code Article 489 paragraph (1), Article 406 paragraph (1), and Article 160 of the Criminal Code.